Spanish Workers' Fund : inter-departmental correspondence (copy) - Parkin, E. G.
029-0088-001 E. PARKIN FINANCE SIR WALTER CITRINE 29th November, 1937. SPANISH WORKERS' FUND. The last direct payment which we made to the I.F.T.U. from the Spanish Workers' Fund was £540 remitted in April last. The present balance standing to the credit of this Fund including the appeal for the Basque Children is upwards of £9,000. 292/946/29/88